Analisis Pengaruh Beta Saham, Debt To Equity Rasio (DER) terhadap Return On Asset (ROA) Perusahaan di Bursa Efek Indonesia - Muhammad Ikhsan; Eko Budi Santoso (Jurnal Ekonomi, 2019)
Calculation of finance ratios is important for the company. Investors can view the performance of the company if the company performs well compared to the average industry. The ratio is a measure of the ratio between account in the financial statements with another accounts. For example profitability ratios Return on Assets( ROA) higher is better because Net income increasing. Likewise with Debt to Equity ratio, is how much restriction ideal loanlikethe ideal size of financial leverage to maximum net income. Beta is a systematic risk obtained from the slope of the regression results between excess stock returns with excess return of the capital market index. This is a measure of risk in stock investing. Risk is something that deviates from the target that we want or something less achievement from thing or something we want or expect. Examples of investment risk is if we suffer any loss of money that we invest. Risks of invest stocks is a systematic risk or a unsystematis risk for examplelike a management in the company. Systematic risk is also called market risk hapend to all shares like outside influence,for example inflation, foreign exchange rates or government policy. This research will address the influence Debt to equity ratio and beta stocks / systematic risk to the value of Return of Asset (ROA) because for the company's net income is important for investors to decide buy shares. Sample data is retrieved author as many as 35 kinds of stocks by taking random stocks that exist in the Indonesian Stock Exchange. The sample data will be processed with statistical information in the answer problems with SPSS applications editions 19. Results of this research is jointly variable Debt to Equity ratio with Beta stocks have a significant influence on Return on Equity (ROA) companies in Indonesia Stock Exchange